Comparison between alkali heat treatment and sprayed hydroxyapatite coating on thermally‐sprayed rough Ti surface in rabbit model: Effects on bone‐bonding ability and osteoconductivity. Issue 5 (20th September 2014) - Kawai, Toshiyuki; Takemoto, Mitsuru; Fujibayashi, Shunsuke; Tanaka, Masashi; Akiyama, Haruhiko; Nakamura, Takashi; Matsuda, Shuichi
Abstract In this study, we investigated the effect of different surface treatments (hydroxyapatite (HA) coating, alkali heat treatment, and no treatment) on the ability of bone to bond to a rough arc‐sprayed Ti metal surface, using rabbit models. The bone‐to‐implant contacts for untreated, HA‐coated, and alkali heat‐treated implants were 21.2%, 72.1%, and 33.8% at 4 weeks, 21.8%, 70.9%, and 30.0% at 8 weeks, and 16.3%, 70.2%, and 29.9% at 16 weeks, respectively (n = 8). HA ‐coated implants showed significantly higher bone‐to‐implant contacts than the untreated and alkali heat‐treated implants at all the time point, whereas alkali heat‐treated implants showed significantly higher bone‐to‐implant contacts than untreated implants at 4 and 16 weeks. The failure loads in a mechanical test for untreated, HA coated, alkali heat‐treated plates were 65.4 N, 70.7 N, and 90.8 N at 4 weeks, 76.1 N, 64.7 N, and 104.8 N at 8 weeks and 88.7 N, 92.6 N, and 118.5 N at 16 weeks, respectively (n = 8). The alkali heat‐treated plates showed significantly higher failure loads than HA‐coated plates at 8 and 16 weeks. The difference between HA‐coated plates and untreated plates were not statistically significant at any time point. Thus HA coating, although it enables high bone‐to‐implant contact, may not enhance the bone‐bonding properties of thermally‐sprayed rough Ti metal surfaces. In contrast, alkali heat treatment can be successfully applied to thermally‐sprayed Ti metal to enhance both bone‐to‐implant contact and bone‐bonding strength. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 103B: 1069–1081, 2015.